Role of autophagy in the periodontal ligament reconstruction during orthodontic tooth movement in rats - Jie Xu; Xian Zhao; Jin Zeng; Jing-Hong Yu; Simon Guan; Xiao-Mei Xu; Li Mei (Elsevier, 2020)
Background/purpose: Autophagy, a lysosome-based degradation pathway that is reportedly activated by mechanical stress and nutrient deprivation, plays an important role in various physiological and pathological events. The present study investigated the level of autophagy and tumor necrosis factor-α(TNF-α) expression in the periodontal ligaments (PDLs) of Sprague-Dawley (SD) rats to analyze the involvement of autophagy and inflammatory cytokines in orthodontic tooth movement (OTM) and maintaining periodontal tissue homeostasis. Materials and methods: SD rats (n = 100) were randomly divided into a control group (n = 10) and an experimental group (n = 90). An orthodontic appliance was placed in each rat in the experimental group, and 10 rats were randomly euthanized 15 min, 30 min, 1 h, 2 h, 4 h, 12 h, 1 d, 3 d and 7 d after mechanical loading. The OTM distance was then measured. Hematoxylin and eosin (HE) staining was used to analyze the morphology of the PDL. Immunohistochemical (IHC) staining and tartrate-resistant acid phosphatase (TRAP) staining were also performed. Results: After the application of orthodontic force and under the dual effects of mechanical force and starvation caused by compressed vessels, the level of autophagy and TNF-α expression in the PDL fluctuated and exhibited a similar trend. Conclusion: Our data suggest a significant correlation between the initiation of autophagy and TNF-α expression, which both exerted positive effects on PDL remodeling during OTM in rats.